PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN MATEMATIS SISWA KELAS X A SMAN 2 ABIANSEMAL - I Wayan Edi Ari Suandana; I Made Surat; Ika Desi Budiarti (Widyadari, 2024)
Teachers have used learning models that can stimulate students to think critically and creatively. However, many students are weak in their creative thinking abilities. The aim of this research is to determine student responses and the application of the Project based learning model in improving creative and mathematical thinking skills in statistics material. This type of research is classroom action research. Research method with descriptive analysis. The subjects of this classroom action research were class XA students of SMA Negeri 2 Abiansemal in the even semester of the 2023/2024 academic year. The object of this research is the application of the project based learning model and student responses to student mathematics learning outcomes. The research used two cycles and each cycle consisted of four stages, namely planning, action, observation and reflection evaluation. The research results show that there is an increase in learning outcomes and observation of responses in each cycle. Pre-cycle learning outcomes 65.35; in cycle I it was 70.27; cycle II was 77.67. Student response results in cycle I were 68.93 and in cycle II were 78.15. Thus, the application of the PjBL learning model can improve students' creative and mathematical thinking abilities and there is a positive student response to the application of the PjBL learning model in improving students' mathematics learning outcomes in statistics material.